Chilli Chill - Jaafar, Anis Izzati; Mohd Yusof, Khalid Alwalid; Fauzi, Muhammad Haziq; Azhar, Nor Azreen; A.Morris, Nur Umairah Fathiah (2016)
TwinGo Corporation is a partnership business that specializes in producing and supplying a specific, imported chili called "cili bara," which is originally from Sumatera, Indonesia. The farm is located at No 18, Jalan Gadong Jaya, Taman Gadong Jaya, 71900 Labu, Negeri Sembilan. The company strategically sells its product primarily through supermarkets, hypermarkets, and convenience stores as these locations are ideal for promoting groceries. The business is funded by a total capital contribution of RM 100,000.00 from its five partners: the General Manager, Administration Manager, Financial Manager, Marketing Manager, and Operational Manager. The General Manager contributes 24% of the equity, while the other four managers each contribute 19%. Although the chili supply market has existing competitors, TwinGo Corporation's competitive advantage lies in its upgrade of the business model—producing and supplying the imported "cili bara," rather than the common cili padi. The company sees significant potential for success and is confident it will successfully compete in the market in the coming years.